RESPON PENAMBAHAN MINERAL KALSIUM, PHOSPOR, MAGNESIUM DAN SULFUR TERHADAP KARAKTERISTIK CAIRAN RUMEN PADA TERNAK KAMBING LOKAL - Triani Adelina (State Islamic University of Sultan Syarif Kasim Riau, 2007)
Microbial growth and various fermentation processes in the rumen require an adequate supply of minerals. An experiment was conducted to detennine rumen fluid characteristics of goal They were randomly allocated into 4 treatments in a Randomized Block Design with 5 replications. Treatments were: A .. forages (natural grasses, gliriddia and leucaenJl) and concentrate (rice brand, com grain and coconut meal); B '